The Tree Valuation Method as a Tool for Supporting Greenway Planning and Development. Case study: Section of Central Highway in Gliwice, Poland - Magdalena Błaszczyk; Marzena Suchocka (Fábos Conference on Landscape and Greenway Planning, 2016)
Tree valuation is a tool determining proper and sustainable urban forest management. The valuation is also important for roads and highways planning, especially those functioning as greenways and greenbelts. In Poland, tree valuation is particularly important because of an intensive development of road network. In the last decade 2000 km of motorways and expressways and 1400 km of national roads were built. Rapid development, urban sprawl and autodependent housing in urban and suburban areas have been affecting the city of Gliwice. In general, urban development has taken precedence over land-use planning because natural capital and its ecosystem services in Poland are undervalued. The road network development is strictly related with tree logging and thus determines the need for tree value estimation, also during their partial damage during construction as a tool of proper urban forest management.
Keywords: greenways; poland; tree valuation; urban forestry